2024
DOI: 10.3389/fimmu.2024.1352744
|View full text |Cite
|
Sign up to set email alerts
|

The gastrointestinal microbiota in the development of ME/CFS: a critical view and potential perspectives

Andreas Stallmach,
Stefanie Quickert,
Christian Puta
et al.

Abstract: Like other infections, a SARS-CoV-2 infection can also trigger Post-Acute Infection Syndromes (PAIS), which often progress into myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). ME/CFS, characterized by post-exercise malaise (PEM), is a severe multisystemic disease for which specific diagnostic markers or therapeutic concepts have not been established. Despite numerous indications of post-infectious neurological, immunological, endocrinal, and metabolic deviations, the exact causes and pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Various viral infections can trigger low-grade inflammation, including: Post-Acute Infectious Syndromes (PAIS): This relatively new medical term refers to symptoms of long-term consequences of acute infections caused by numerous pathogenic agents, including viruses such as SARS-CoV-2 [ 144 ]. The main manifestations of PAIS encompass general poor functional status, exercise intolerance, debilitating fatigue, signs of depression, cognitive and sensory impairments, dysautonomia, musculoskeletal complaints, flu-like symptoms, as well as disturbances in gut microbiota and various immunologic dysfunctions [ 144 , 145 ]. Besides SARS-CoV-2, other viruses like Ebola, Dengue, Polio, SARS (SARS-CoV-1), Chikungunya, EBV, West Nile virus, and potentially alphaviruses, Ross River virus, and VZV have also been implicated in initiating PAIS [ 144 ].…”
Section: Low-grade Inflammation In Long Covid and Other Viral Infectionsmentioning
confidence: 99%
“…Various viral infections can trigger low-grade inflammation, including: Post-Acute Infectious Syndromes (PAIS): This relatively new medical term refers to symptoms of long-term consequences of acute infections caused by numerous pathogenic agents, including viruses such as SARS-CoV-2 [ 144 ]. The main manifestations of PAIS encompass general poor functional status, exercise intolerance, debilitating fatigue, signs of depression, cognitive and sensory impairments, dysautonomia, musculoskeletal complaints, flu-like symptoms, as well as disturbances in gut microbiota and various immunologic dysfunctions [ 144 , 145 ]. Besides SARS-CoV-2, other viruses like Ebola, Dengue, Polio, SARS (SARS-CoV-1), Chikungunya, EBV, West Nile virus, and potentially alphaviruses, Ross River virus, and VZV have also been implicated in initiating PAIS [ 144 ].…”
Section: Low-grade Inflammation In Long Covid and Other Viral Infectionsmentioning
confidence: 99%
“…Patients with inflammatory bowel disease often experience depression, which is indicated by various markers of leaky gut such as calprotectin and LBP [41]. There have been studies conducted on MDD and CFS that have found evidence of gut dysbiosis endotypes, which suggest an association with increased gut permeability and pro-inflammatory potential [42][43][44][45][46].…”
Section: The Paracellular Pathway and Long Covidmentioning
confidence: 99%
“…Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a debilitating chronic condition that manifests in various physiological systems and is characterized by unresolved fatigue and post-exertional symptom exacerbation (PESE) [ 1 , 2 ]. The onset of ME/CFS is often connected to viral/bacterial infection [ 3 , 4 ], with the herpesviruses being most implicated [ 5 7 ]. However, there are no widely-established clinical biomarkers for the condition and much of the disease pathogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%